An Epidemiological Update on Indoor Tanning and the Risk of Skin Cancers - Clio Dessinioti; Alexander J. Stratigos (Current Oncology, 2022)
Indoor tanning (sunbeds, solarium) uses artificial ultraviolet radiation (UVR) to stimulate cosmetic tanning of the skin. Indoor tanning has been officially classified as a human carcinogen in 2009 by the International Agency for Research on Cancer of the World Health Organization (WHO). The differences in the prevalence of sunbed use across countries and over the years highlight underlying legislative, climatic, and cultural differences. Indoor tanning-seeking behaviors may be driven by motivations for an appealing appearance, largely influenced by gender and age, and several misconceptions that a prevacation tan safeguards the skin, that sunbeds can be used to treat acne or to increase vitamin D, or that tanning is a healthy habit. This review provides an epidemiological update on the prevalence of sunbed use, who tends to use sunbeds and why, and details the current evidence on the association of sunbeds with skin cancers, including cutaneous melanoma, basal cell carcinoma (BCC), and cutaneous squamous cell carcinoma (cSCC). A statistically significant higher risk of cutaneous melanoma, BCC and cSCC with the use of sunbeds has been consistently demonstrated. This risk of skin cancer is even higher with the more frequent use of sunbeds, underscoring a dose–response relationship, and in those first exposed to sunbeds at a younger age. Preventive measures against sunbed use include legislation restricting sunbed use, educational campaigns to inform and discourage from indoor tanning, as well as using the internet, online advertising messages and the social media to reach larger audiences and to promote an untanned appearance.